Control of automatic fire extinguishing operation for 5 forest areas with SCADA - Ustundag, Aybike; Gencer, Cetin (Institute of Electrical and Electronics Engineers Inc., 2021)
The number of forest fires has increased significantly in recent years. Interventions to forest fires from air and land are very difficult and dangerous. In addition, since these interventions are time-consuming, forest fire can spread to a much wider area. In this study, an automatic fire extinguishing system was designed using SCADA for 5 forest regions up to 5 hectares. In the event of a fire in the system, the smoke sensor in the fire area becomes active and the IP camera image in this area is displayed on the screen. The pressurized water flushing tap, which automatically rotates 360 degrees, works in the area. If desired, automatic operation can be canceled and manually adjusted water flushing tap can be operated. The system gives a warning when the tank water drops below 1 ton. The aim of this study is to automatically intervene early in any fire that may occur in the forest and to control the fire before it spreads. © 2021 IEEE.
5h International Symposium on Multidisciplinary Studies and Innovative Technologies, ISMSIT 2021 -- 21 October 2021 through 23 October 2021 -- Ankara -- 174473
Keywords: Forest fires; PLC; SCADA